ANALISIS MANFAAT BANTUAN USAHA EKONOMI PRODUKTIF KOTA PALU DAN KABUPATEN SIGI - Fardillah Yuyu Wahyuni; Muhammad Yunus Kasim; Yohan Yohan; Yunus Sading; Rita Yunus (Ensiklopedia of Journal, 2026)
Poverty in Central Sulawesi remains above the national average, prompting the Productive Economic Enterprise (UEP) assistance programme as an empowerment strategy. This study analyses the benefit of UEP assistance and its feasibility in Palu City and Sigi Regency for 2022–2024. Using a descriptive mixed-methods design with 57 respondents selected through the Slovin formula, data were analysed using utility theory and Benefit-Cost Ratio (BCR). Results show that average income rose by IDR 842,982 per month (44.3%), with 89.5% of recipients gaining income. The overall BCR was 0.6267 (1), economically not yet feasible within one year; however, Sigi Regency recorded a BCR of 1.0480 (1). The programme is socially feasible and recommended to continue with strengthened mentoring.Keywords: benefit-cost ratio; poverty alleviation; productive economic enterprise; utility; welfare